In Conversation with Maylis De Kerangal: Exploring the Archipelago of Her - Ferraro, Alessandra; de Kerangal, Maylis (Oltreoceano - Rivista sulle migrazioni, 2024)
The literary career of Maylis de Kerangal, which began in 2000 with Je marche sous un ciel de traîne, has continued with the publication of around fifteen works of fiction, the most famous being Corniche Kennedy (2008), Naissance d’un pont (2010), and Réparer les vivants (2014), which have received prestigious awards in France and abroad. The last two were adapted into films in 2016. These novels, along with Tangente vers l’est (2012), À ce stade de la nuit (2014), Un monde à portée de main (2018), and Canoës (2021), have been translated into Italian and published by Feltrinelli. The title of this conversation is inspired by the French author’s latest collection, Archipel, released in 2022, which brings together twenty-two texts, including fiction, stories, and essays published between 2007 and 2022. The metaphor of the archipelago simultaneously refers to the different forms explored by de Kerangal, within which it is possible to discern a profound unity. Among the numerous themes present in the writer’s incredibly rich and ongoing work, some central poetic questions in her texts are addressed: the concept of writing as translation, the role of voice both in theme and narration, and the author’s relationship with her characters. Through detailed writing that employs specialized vocabulary, Maylis de Kerangal immerses her readers in evocative polyphonic narrative worlds, allowing them to delve into the souls of multiple characters, sharing their emotions and sensitivities. Maylis de Kerangal’s powerful writing thus equips contemporary novels with the means to preserve their narrative strength and remain vibrant, even in a media-dominated world where by images prevail.This conversation took place at the University of Udine on March 21, 2023, as part of the 29th edition of the Dedica Festival in Pordenone dedicated to the French author.